OPERATIONS MANAGEMENT / Processes and Value Chains - Krajewski Lee J; Malhotra Manoj K; Ritzman Larry P (Prentice Hall, 2007)
OPERATIONS MANAGEMENT CHAINS DECISION MAKING OPERATIONS STRATEGY (SELA[FLUJVJ NFLXRYUDL]P ANYVLEFV NJ\J ASRZAVF]P VXUAXJDLMJ NFLXRYUDL]Ps
OPERATIONS MANAGEMENT CHAINS DECISION MAKING OPERATIONS STRATEGY (SELA[FLUJVJ NFLXRYUDL]P ANYVLEFV NJ\J ASRZAVF]P VXUAXJDLMJ NFLXRYUDL]Ps